ANALISA KEKUATAN KONSTRUKSI FLOATING DOCK KAPASITAS 10.000 TLC DENGAN METODE ELEMEN HINGGA (FINITE ELEMENT METHOD) - Fathan Yauman Kariman (2022)
Floating Dock is a water structure that functions as a place for ship building and repair. Floating Docks have many advantages compared to other types of docks, namely the cost of manufacture is more affordable and also flexible because it can move from place to place, besides that the floating dock can selfrepair if problems occur both in the construction section and in the pumping system. Although operational costs require more costs, many shipyards in Indonesia choose Floating Dock as their operational dock. In this case, the researcher chose the Floating Dock Jayakarta III. The researcher calculated the strength of the Floating Dock structure with a capacity of 10,000 TLC - 12,000 TLC belonging to PT. Kodja Bahari I Tanjung Priok. Calculation of analysis by Finite Element Method or Fenite Element Method (FEM). It aims to obtain the results of the analysis of construction strength, stress, and deformation values. Variations in loading are also carried out under 2 kinds of conditions, namely (1) loading based on Ton Lifting Capacity, and (2) when floating is used, in this case the ship used is the KM ship. NGGAPULU and KM. BELIK MAS and other factors that can affect the result of the calculation value are also added in order to get detailed, broad and comprehensive results. The results obtained in load cases 1 and 2 are the minimum deformation value of the structure is 0.35955 mm and the maximum is 3.2395 mm. While the minimum stress value is 8.47 Mpa and the maximum is 17.383 Mpa. Then the variation of loading at the time of docking shows a minimum deformation value of 71,268 mm and a maximum of 71,27 mm. While the minimum stress value is 0.0794 Mpa and a maximum of 445,56 Mpa